2021
DOI: 10.1186/s40468-021-00119-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using online language-support resources on L2 writing performance

Abstract: Language learners today have access to a much wider choice of resources and language-support tools that aid their writing processes. While research on the convenience and flexibility of the writing resources that learners use in real-life writing activities have argued for a re-conceptualization of writing ability, little is known about the effect of using them in a writing assessment setting. Accordingly, the present study aimed to examine whether L2 learners’ use of writing resources in a writing test might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Positive elements can be an extension of research studies conducted before the pandemic which advocated the benefits of L2 remote online writing (Godwin-Jones, 2018;Griffith, 2014;Han & Shin, 2017) or they can be the result of studies conducted post Covid-19 where new parameters of benefits may have been manifested and experienced by L2 teachers as a result of online teaching and assessment during the pandemic (Balouchi & Samad, 2021). Shin et al (2021) affirm that L2 students find it more convenient to use various language-support resources available online. They found that students who had access to online writing resources outperformed those students who were not given access to such resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Positive elements can be an extension of research studies conducted before the pandemic which advocated the benefits of L2 remote online writing (Godwin-Jones, 2018;Griffith, 2014;Han & Shin, 2017) or they can be the result of studies conducted post Covid-19 where new parameters of benefits may have been manifested and experienced by L2 teachers as a result of online teaching and assessment during the pandemic (Balouchi & Samad, 2021). Shin et al (2021) affirm that L2 students find it more convenient to use various language-support resources available online. They found that students who had access to online writing resources outperformed those students who were not given access to such resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technological advances have had a significant effect on teaching and learning in the business sector and educational settings, including writing (Shin et al, 2021). Many writing tools are available for personal, professional, and academic use (Skovhus, & Poulsen, 2021).…”
Section: Connectivism and Mobile Technologymentioning
confidence: 99%
“…They also benefited from the advantages of mixing face-to-face instruction and online experiences and had invaluable opportunities to produce and generate related ideas during the pre-writing process. Online resources facilitated students' brainstorming and gathering information that ultimately improved the content of the writing genres (Rashtchi & Porkar, 2020;Shin et al, 2021). Moreover, the hybrid learning model developed students' language use since it provided opportunities for students to work individually and collaboratively inside the classroom and online.…”
Section: Journal Of Language Teaching and Researchmentioning
confidence: 99%